The immunosuppressive and pro-tumor functions of CCL18 at the tumor microenvironment. (August 2021) - Cardoso, Ana Patrícia; Pinto, Marta Laranjeiro; Castro, Flávia; Costa, Ângela Margarida; Marques-Magalhães, Ângela; Canha-Borges, Ana; Cruz, Tânia; Velho, Sérgia; Oliveira, Maria José
Graphical abstract: Highlights: Chemokines orchestrate the immune architecture of tumors, influencing progression. CCL18 is highly expressed in several tumors. CCL18 promotes an immunosuppressive microenvironment and cancer cell invasion. CCL18 has been correlated with poor prognosis in several types of cancer. This chemokine is a promising biomarker/ therapeutic target in solid cancers. Abstract: Chemokines are essential mediators of immune cell trafficking. In a tumor microenvironment context, chemotactic cytokines are known to regulate the migration, positioning and interaction of different cell subsets with both anti- and pro-tumor functions. Additionally, chemokines have critical roles regarding non-immune cells, highlighting their importance in tumor growth and progression. CCL18 is a primate-specific chemokine produced by macrophages and dendritic cells. This chemokine presents both constitutive and inducible expression. It is mainly associated with a tolerogenic response and involved in maintaining homeostasis of the immune system under physiological conditions. Recently, CCL18 has been noticed as an important component of the complex chemokine system involved in the biology of tumors. This chemokine induces T regulatory cell differentiation and recruitment to the tumor milieu, with subsequent induction of a pro-tumor (M2-like) macrophage phenotype. CCL18 is also directly involved in cancer cell-invasion, migration, epithelial-to-mesenchymal transition and angiogenesis stimulation, pinpointing an important role in the promotion of cancer progression. Interestingly, this chemokine is highly expressed in tumor tissues, particularly at the invasive front of more advanced stages (e.g. colorectal cancer), and high levels are detected in the serum of patients, correlating with poor prognosis. Despite the promising role of CCL18 as a biomarker and/or therapeutic target to hamper disease progression, its pleiotropic functions in a context of cancer are still poorly explored. The scarce knowledge concerning the receptors for this chemokine, together with the insufficient insight on the downstream signaling pathways, have impaired the selection of this molecule as an immediate target for translational research. In this Review, we will discuss recent findings concerning the role of CCL18 in cancer, integrate recently disclosed molecular mechanisms and compile data from current clinical studies.